Characterization of the complete chloroplast genome of Sinosenecio oldhamianus (Compositae) - Jingjing Xu; Yihua Gong; Guoqian Hao (Mitochondrial DNA. Part B. Resources, 2019)
The complete chloroplast (cp) genome sequence of Sinosenecio oldhamianus, a common medicinal plant is widely distributed in South China. The plastome is 150,926 bp in length, with one large single-copy region of 94,588 bp, one small single-copy region of 18,130 bp, and two inverted repeat (IR) regions of 24,852 bp. It contains 134 genes, including 87 protein-coding genes, 8 ribosomal RNA, and 37 transfer RNA. The phylogenetic tree shows that this species is a sister to the genus Ligularia. The published plastome within Sinosenecio provides significant insight for elucidating the phylogenetic relationship of taxa within tribe Compositae.